Harnessing synergistic metabolism: Bioelectricity and color removal from palm oil mill effluent in bacteria consortium – microalgae microbial fuel cell - Kongthong, Alisa; Chaijak, Pimprapa (Brawijaya University, 2024)
This study investigated the application of a microbial fuel cell (MFC) system integrated with freshwater microalgae Chlorella sp. TSU-FF67for wastewater treatment, electricity generation, and bio-oil production. The MFC with Chlorella sp. TSU-FF67achieved a significantly higher open-circuit voltage (OCV) of 413.67 ± 15.67 mV compared to the control (13.33 ± 6.38 mV), indicating enhanced bioelectrocatalytic activity. The system also demonstrated efficient organic matter removal from palm oil mill effluent (POME) with a maximum color removal of 95.12 ± 3.50%. Furthermore, Chlorella sp. TSU-FF67 recovered from the PMFC exhibited a remarkable docosahexaenoic acid (DHA) yield of 1,932.28 ± 88.69 µg/mL (1.93 ± 0.08 mg/mL), highlighting its potential as a feedstock for bio-oil production. This work presents a promising approach for sustainable wastewater treatment while simultaneously generating bioelectricity and bio-oil using microalgae-MFC integration.